2015
DOI: 10.1021/acs.jpca.5b05155
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thermal Conversion of Conjugated Polymers Investigated from Their Optical Absorption Spectra

Abstract: We report on a phenomenological, theoretical model to calculate the rate constants and activation energies for the thermal conversion reactions from poly(xylylidene tetrahydrothiophenium chloride) (PTHT) into poly(p-phenylenevinylene) (PPV) using the optical absorption spectra of spin-coated films. The probabilities of electron transitions were calculated considering Franck-Condon states with a Gaussian distribution of conjugated segments and molecular excitons. The dependence on the conjugation degree (n) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The Langmuir–Blodgett PPV film (LB-PPV) was produced using 20 Z-type layers of PTHT and DBS (1:1 w/w) solution dissolved in 1,2-dichloromethane and ethanol (1:1 v/v). The SC-PPV and LB-PPV films were obtained after thermal conversion of SC-PTHT+DBS and LB-PTHT+DBS at 110 °C for 2 h under 10 –1 mbar vacuum . Absorbance spectra in the UV–vis range for both samples were obtained at 10 K using the spectrometer Hitachi U-2001 and a closed circuit helium cryostat.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The Langmuir–Blodgett PPV film (LB-PPV) was produced using 20 Z-type layers of PTHT and DBS (1:1 w/w) solution dissolved in 1,2-dichloromethane and ethanol (1:1 v/v). The SC-PPV and LB-PPV films were obtained after thermal conversion of SC-PTHT+DBS and LB-PTHT+DBS at 110 °C for 2 h under 10 –1 mbar vacuum . Absorbance spectra in the UV–vis range for both samples were obtained at 10 K using the spectrometer Hitachi U-2001 and a closed circuit helium cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…Density matrix renormalization group calculations of Barford and co-workers showed that the energy gap of linear chains of PPV with n repeat units is well parametrized by where E ∞ is the infinite chain energy gap and ϵ is an adjustable parameter. Based on fittings of experimental PPV absorption spectra taken from the literature, we used E ∞ = 2.18 eV and ϵ = 2.00 eV for our PPV oligomers. In Figure SI3 of the Support Information, we show that eq also fits well the gaps of other phenyl-based conjugated polymers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations